The Blonde d'Aquitaine T3811>G3811 mutation in the myostatin gene: association with growth, carcass, and muscle phenotypes in veal calves. (6th February 2021) - Vinet, Aurélie; Bouyer, Claire; Forestier, Lionel; Oulmouden, Ahmad; Blanquet, Véronique; Picard, Brigitte; Cassar-Malek, Isabelle; Bonnet, Muriel; Rocha, Dominique; Renand, Gilles
Abstract: The mutation T3811 → G3811 (TG3811) discovered in the myostatin gene of the Blonde d'Aquitaine breed is suspected of contributing to the outstanding muscularity of this breed. An experiment was designed to estimate the effect of this mutation in an F2 and back-cross Blonde d'Aquitaine × Holstein population. By genotyping all known mutations in the myostatin gene, it was ensured that the TG3811 mutation was indeed the only known mutation segregating in this population. Fifty-six calves (43 F2, 13 back-cross) were intensively fattened and slaughtered at 24.0 ± 1.4 wk of age. The effects of the mutation were estimated by comparing the calves with the [T/T] ( n = 18), [T/G] ( n = 30), and [G/G] ( n = 8) genotypes. Highly significant substitution effects ( P < 0.001), above + 1.2 phenotypic SD, were shown on carcass yield and muscularity scores. Birth weight ( P < 0.001) was positively affected by the mutation (+0.8 SD) but not growth rate ( P = 0.97), while carcass length ( P = 0.03), and fatness ( P ≤ 0.03) were negatively affected (–0.5 to –0.7 SD). The characteristics of the Triceps brachii muscle were affected by the mutation ( P < 0.001), with lower ICDH activity (oxidative) and a higher proportion of myosin type 2X muscle fibers (fast twitch). The effects of the TG3811 mutation were similar to those of other known myostatin mutations, although the Blonde d'Aquitaine animals, which are predominantly [G/G] homozygous, do not exhibit extreme double muscling.